2013
DOI: 10.1021/es3035347
|View full text |Cite
|
Sign up to set email alerts
|

Sulfidation Mechanism for Zinc Oxide Nanoparticles and the Effect of Sulfidation on Their Solubility

Abstract: Environmental transformations of nanoparticles (NPs) affect their properties and toxicity potential. Sulfidation is an important transformation process affecting the fate of NPs containing metal cations with an affinity for sulfide. Here, the extent and mechanism of sulfidation of ZnO NPs were investigated, and the properties of resulting products were carefully characterized. Synchrotron X-ray absorption spectroscopy and X-ray diffraction analysis reveal that transformation of ZnO to ZnS occurs readily at amb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
144
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(161 citation statements)
references
References 39 publications
12
144
2
3
Order By: Relevance
“…For ZnO, close to 100 % was converted to ZnS within 5 days in the presence of sufficient sulfide concentrations (Ma et al 2013). Similarly, for Ag, in systems with a ratio of S/Ag as low as 0.2, more than 15 % of the Ag is found as Ag 2 S within 24 h (Levard et al 2011).…”
Section: Transformationsmentioning
confidence: 96%
See 2 more Smart Citations
“…For ZnO, close to 100 % was converted to ZnS within 5 days in the presence of sufficient sulfide concentrations (Ma et al 2013). Similarly, for Ag, in systems with a ratio of S/Ag as low as 0.2, more than 15 % of the Ag is found as Ag 2 S within 24 h (Levard et al 2011).…”
Section: Transformationsmentioning
confidence: 96%
“…Similarly, for Ag, in systems with a ratio of S/Ag as low as 0.2, more than 15 % of the Ag is found as Ag 2 S within 24 h (Levard et al 2011). The presence of sulfides may also cause rapid aggregation and sedimentation (Ma et al 2013). This concurs with the fact that the point-of-zero charge increases with increasing sulfur for Ag, though this will not necessarily lead to an increase in aggregation (Levard et al 2011).…”
Section: Transformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an indirect indication that dissolution characteristics play an important role in the increased toxicity of CuS-NPs relative to CuO-NPs in medaka embryos, which contrasts with previous studies on that sulfidation reduced dissolution of metallic NPs due to the lower solubility of metal sulfides. [19][20][21][22]42 Also, it contradicts the solubility products (K sp ) of CuS (8 × 10 −37 ) and CuO (1 × 10 −7 ) in solutions. As shown in Figure 4, CuS-NPs show higher extent of dissolution relative to CuO-NPs could be attributed to not only the oxidation dissolution of the formed CuS-NPs, but also the presence of CuS clusters.…”
Section: ■ Discussionmentioning
confidence: 97%
“…Recently, much attention has been paid to chemical transformations of ENPs in the environment, which will result in largely unknown end products and affect the fate and potential toxicity of ENPs in the environment [4]. For example, studies have demonstrated the transformation of ZnO NPs to ZnS in the presence of sodium sulfide (Na 2 S) or hydrogen sulfide (H 2 S) [12,13]. Our previous research [14] has confirmed that phosphate ions can induce the transformation of ZnO NPs to tetrahydrate Zn 3 (PO 4 ) 2 in aqueous solutions at room temperature and under neutral pH conditions.…”
Section: Introductionmentioning
confidence: 99%